Determination of the reference interval for urinary klotho to creatinine ratio of healthy dogs - Marečáková, Nikola; Kačírová, Jana; Tóthová, Csilla; Maďari, Aladár; Maďar, Marián; Farbáková, Jana; Horňák, Slavomír (Frontiers in Veterinary Science, 2024)
For several years, alpha klotho has been considered as a candidate biomarker in chronic kidney disease (CKD), progression of CKD and CKD mineral bone disorders (CKD-MBD). The evidence on the relationship between klotho and kidney function is controversial in some areas. The aim of the study was to identify the influence of age, sex and breed on urinary alpha klotho, values in the early stages of CKD within the studied population and determine a reference interval in a group of healthy dogs. Significantly higher values were measured in older dogs over 6 years old (P = 0.026, P = 0.0007) and in the breed German Shepherd than Belgian Shepherd (P = 0.0401). On the basis of sex and in small breed dogs, no significant differences were noted. In dogs with CKD stage 2, alpha klotho values were significantly lower (P = 0.0135) than in healthy dogs. Within the studied population, a reference interval for alpha klotho in urine (UrKl/Cr) was determined in the range of 3.94 – 23.55 pg/gCr. Since our findings show that alpha klotho is associated with older age, we assume that this may have influenced the results in the group of dogs with CKD stage 1 due to the presence of predominantly old dogs in this group. Future studies would be needed to consider age as a factor affecting urinary alpha klotho in dogs with CKD.